Sei sulla pagina 1di 5

RESPUESTAS AL SEGUNDO EXAMEN DE CÁLCULO

𝑥 2 − 2√𝑥
1) 𝑦=
𝑥

𝑥 2 2√𝑥 1
𝑦= − = 𝑥 − 2𝑥 −2
𝑥 𝑥
1 3
𝑦 ′ = 1 − 2 (− ) 𝑥 −2
2

3
𝑦 ′ = 1 + 𝑥 −2

1
𝑦′ = 1 + 3
𝑥2

1
𝑦′ = 1 +
√𝑥 3

1
5 5 7
7
4 + 𝑠𝑒𝑛 8𝑥 4 + 𝑠𝑒𝑛 (8𝑥)
2) 𝑓(𝑥) = 𝐿𝑛 √( ) = 𝐿𝑛 (( ) )
4 − cos 8𝑥 4 − cos (8𝑥)

5
4 + 𝑠𝑒𝑛 (8𝑥) 7 5 4 + 𝑠𝑒𝑛 (8𝑥)
= 𝐿𝑛 ( ) = 𝐿𝑛 ( )
4 − cos (8𝑥) 7 4 − cos (8𝑥)

5
= [𝐿𝑛 (4 + 𝑠𝑒𝑛 (8𝑥)) − 𝐿𝑛 (4 − cos (8𝑥))]
7

5 1 1
𝑓 ′ (𝑥) = [ (8 cos(8𝑥)) + (8 𝑠𝑒𝑛 (8𝑥))]
7 4 + 𝑠𝑒𝑛 (8𝑥) 4 − cos 8𝑥
5 8 cos(8𝑥) 8 𝑠𝑒𝑛 (8𝑥)
𝑓 ′ (𝑥) = [ + ]
7 4 + 𝑠𝑒𝑛 (8𝑥) 4 − cos (8𝑥)

𝑥
𝑥 1 𝑥2
3) 𝑓(𝑥) = 𝑐 = 𝑥2 + 𝑐 = 𝑥2 + 𝑐
𝑥+
𝑥 𝑥

(𝑥 2 + 𝑐)(2𝑥) − (𝑥 2 )(2𝑥)
𝑓 ′ (𝑥) =
(𝑥 2 + 𝑐)2

2𝑥 3 + 2𝑐𝑥 − 2𝑥 3 2𝑐𝑥
𝑓 ′ (𝑥) = 2 2
= 2
(𝑥 + 𝑐) (𝑥 + 𝑐)2

5𝑒 2𝑥 + 4𝑒 2𝑥 9𝑒 2𝑥
𝑓(𝑥) = = =9
5𝑒 2𝑥 − 4𝑒 2𝑥 𝑒 2𝑥

𝑓 ′ (𝑥) = 0

4) 5𝑥 2 + 5𝑦 2 = 𝑠𝑒𝑛 (5𝑦 2 ) + cos (4𝑥 2 )

10𝑥 + 10𝑦𝑦 ′ = cos(5𝑥𝑦 2 )(10𝑦𝑦 ′ ) = 𝑠𝑒𝑛 (4𝑥 2 )(8𝑥)

10𝑥 + 10𝑦𝑦 ′ = 10𝑦𝑦 ′ cos(5𝑥 2 ) − 8𝑥 𝑠𝑒𝑛 (4𝑥 2 )

10𝑦𝑦 ′ − 10𝑦𝑦 ′ cos (5𝑦 2 ) = −8𝑦 𝑠𝑒𝑛 (4𝑦 2 ) − 10𝑥

𝑦 ′ (10𝑦 − 10𝑦 cos (5𝑦 2 )) = −8𝑥 𝑠𝑒𝑛 (4𝑥 2 ) − 10𝑥

−8𝑥 𝑠𝑒𝑛 (4𝑥 2 ) − 10𝑥


𝑦′ =
10𝑦 − 10𝑦 cos (5𝑦 2 )

4 + 2𝑥 4 − 2𝑥 (4 + 2𝑥)(4 + 2𝑥) − (4 − 2𝑥)(4 − 2𝑥 3)


5) 𝑓(𝑥) = − =
4 − 2𝑥 4 + 2𝑥 (4 − 2𝑥)(4 + 2𝑥)
16 + 8𝑥 + 8𝑥 + 4𝑥 2 − (16 − 8𝑥 − 8𝑥 + 4𝑥 2 )
=
(4 − 2𝑥)(4 + 2𝑥)

16 + 16𝑥 + 4𝑥 2 − 16 + 16𝑥 − 4𝑥 2 32𝑥


= =
(4 − 2𝑥)(4 + 2𝑥) 16 − 4𝑥 2

32𝑥 8𝑥
= =
4(4 − 𝑥 2 ) 4 − 𝑥2

(4 − 𝑥 2 )(8) − 8𝑥 (−2𝑥)
𝑓 ′ (𝑥) =
(4 − 2𝑥 2 )2

′ (𝑥)
32 − 8𝑥 2 + 16𝑥 2 8(𝑥 2 + 4)
𝑓 = =
(4 − 2𝑥 2 )2 (4 − 2𝑥 2 )2

1
1 2
1 2
6) 𝑓(𝑥) = √𝑥 + √𝑥 + √𝑥 = (𝑥 + (𝑥 + 𝑥 2) )

1
1 −2 1
1 1 2 1 1 −2 1 1
𝑓 ′ (𝑥)
= (𝑥 + (𝑥 + 𝑥 2) ) [1 + (𝑥 + 𝑥 2 ) (1 + 𝑥 −2 )]
2 2 2

1 1 1
𝑓 ′ (𝑥) = . [1 + ∙ (1 + )]
2 √𝑥 + √𝑥 2 √𝑥
2 √𝑥 + √𝑥 + √𝑥

1 1 1
𝑓 ′ (𝑥) = + ∙ (1 + )
2 √𝑥
2 √𝑥 + √𝑥 + √𝑥 [4
√𝑥 + √𝑥 + √𝑥 √𝑥 + √𝑥
]
1 1 1
𝑓 ′ (𝑥) = + +
2 √𝑥 + √𝑥 + √𝑥 4 √𝑥 + √𝑥 + √𝑥 √𝑥 + √𝑥 8 √𝑥 + √𝑥 + √𝑥 √𝑥 + √𝑥 √𝑥

1
𝑎2 − 𝑧 2 𝑎2 − 𝑧 2 2
7) 𝑓(𝑧) = 𝐿𝑛 √ 2 = 𝐿𝑛 ( )
𝑎 + 𝑧2 𝑎2 + 𝑧 2

1
= [𝐿𝑛 (𝑎2 − 𝑧 2 ) − 𝐿𝑛 (𝑎2 + 𝑧 2 )]
2

1 1 1
𝑓 ′ (𝑧) = [ 2 (−2𝑥) − (2𝑧)]
2 𝑎 − 𝑧2 𝑎2 + 𝑧 2

1 −2𝑧 2𝑧
𝑓 ′ (𝑧) = [ 2 2
− 2 ]
2 𝑎 −𝑧 𝑎 + 𝑧2

−𝑧 𝑧
𝑓 ′ (𝑧) = − 2
𝑎2−𝑧 2 𝑎 − 𝑧2

9) 𝑦 = 𝐿𝑛 (𝑒 −𝑥 + 𝑥𝑒 −𝑥 )

1
𝑦′ = [−𝑒 −𝑥 + (𝑥)(−𝑒 −𝑥 ) + (𝑒 −𝑥 )(1)]
𝑒 −𝑥 + 𝑥𝑒 −𝑥

1
𝑦′ = −𝑥 −𝑥
(−𝑒 −𝑧 − 𝑥𝑒 −𝑥 + 𝑒 −𝑥 )
𝑒 + 𝑥𝑒

−𝑥𝑒 −𝑥 𝑒 −𝑥 (−𝑥)
𝑦′ = =
𝑒 −𝑥 + 𝑥𝑒 −𝑥 𝑒 −𝑥 (1 + 𝑥)

−𝑥
𝑦′ =
1+𝑥
10) 𝑓(𝜃) = csc(𝜃) + 𝑒 𝜃 cot(𝜃)

𝑓 ′ (𝜃) = −𝑐𝑜𝑠(𝜃) 𝑐𝑜𝑡(𝜃) + [𝑒 𝜃 (−𝑐𝑠𝑐𝜃) + 𝑐𝑜𝑡(𝜃)𝑒 𝜃 ]

𝑓 ′ (𝜃) = −𝑐𝑠𝑐(𝜃)𝑐𝑜𝑡(𝜃) − 𝑒 𝜃 𝑐𝑠𝑐(𝜃) + 𝑐𝑜𝑡(𝜃)𝑒 𝜃

𝑓 ′ (𝜃) = − csc(𝜃) (cot(𝜃) + 𝑒 𝜃 ) + 𝑒 𝜃 cot(𝜃)